Phylogeny, tissue-specific expression, and activities of root-secreted purple acid phosphatases for P uptake from ATP in P starved poplar - Kavka, Mareike (Plant science : an international journal of experimental plant biology, 2021)
Copyright © 2021 Elsevier B.V. All rights reserved.